Use of Misoprostol for Induction of Labour - Lubna Yasmeen, Tahira Rasheed ,Naheed Bano, Rubina Mubashar (Journal of Rawalpindi Medical College, 2009)
Background: To find out safety and efficacy of Misoprostol in induction of labour at term in women with live fetus through vaginal versus sublingual route Methods: In this cross sectional study, total of 200 pregnant women at term (37-42 week) with live fetus were selected randomly for induction of labour with tab misoprostol. These women were divided in two groups with 100 women in each group. Misoprostol was administered in a dose of 50 microgram (1/4th tab),in group I through vaginal route and in group II through sublingual route. Maximum of three doses were given in 24 hours and resumed on next day if there was no improvement. Results: Number of doses of misoprostol used for induction of labour was less than two in 68% cases in group I and 78% cases in group II, while more than two doses were used in 32%cases in vaginal group and 22% in sublingual group. Administration to induction interval was less than 12 hours in 60% cases in vaginal group and 80% cases in sublingual group. Total duration of labour was less than 8 hours, seen in more cases of sublingual group than vaginal group i.e56% versus 40%. Vaginal delivery was achieved in 60% cases in vaginal group and 70%cases in sublingual group with rate of caesarean section 40% versus 30% respectively. Regarding fetal outcome, fetal distress and meconium stained liquor was seen in 26% and 24% cases in vaginal and sublingual groups respectively, showing no significant difference between two groups. However neonatal intensive care unit(NICU) admissions were more in vaginal group than sublingual group i.e. 30% versus 20%.There were 100% live births in both groups with ENND (early neonatal death)02% in each group. Maternal out come was good in both groups. Uterine hyperstimulation was seen in 02%cases in each group while only two cases of fever were seen in sublingual group. There was no case of post partum haemorrhage (PPH) and no maternal death in both groups.. Conclusion: Misoprostol is effective for induction of labour at term with live fetus, more through sublingual than vaginal route. Its safety and efficacy can be further ensured by using lower dosage regimes. .